Effects of different storage temperatures on microbial spoilage and bacterial community structure of fresh beef by high-throughput sequencing technology - WANG,Xinhui (2023)
Abstract Comparsion of the effects of the chilling (4 ºC), superchilling (-2 ºC) and frozen (-18 ºC) storage on microbial spoilage and bacterial community structure of fresh beef was evaluated by high-throughput sequencing technology in this study. The results indicated that storage temperature can significantly affect the degree of microbial spoilage and bacterial community structure of fresh beef during storage. At the species level, the primary dominant bacterial species in beef samples was Pseudomonas fragi with relative abundance of 37.78% followed by Myroides phaeus and Brochothrix thermosphacta with 10.95% and 4.64%, respectively, at the beginning of storage. Both superchilling and frozen storage can effectively inhibit the growth of P. fragi, while the chilling storage failed to demonstrate strong inhibition for growth of P. fragi. Similar result was found for Myroides phaeus. The chilling, superchilling and frozen storage can not effectively inhibit the growth of Brochothrix thermosphacta and Acinetobacter johnsonii. The difference of microbial spoilage in beef stored in three kinds of storage may be related to the difference of the bacterial community structure and the formation of dominant spoilage bacteria. These results revealed that superchilling and frozen storage can effectively inhibit the formation of dominant spoilage bacteria, resulting in a good freshness preservation.